Targeting Wnt Signaling in the Tumor Immune Microenvironment to Enhancing EpCAM CAR T-Cell therapy - Li, Weizhen; Zhou, Yang; Wu, Zhongen; Shi, Yaoping; Tian, Enming; Zhu, Yingqi; Wang, Tao; Dou, Wei; Meng, Xiangjing; Chen, Ming; Zhai, Bo; Zhu, Di (Frontiers in Pharmacology, 2021)
Metastatic cancer patients are still lacking viable treatments. Chimeric antigen receptor (CAR) T cells have shown promise in hematologic malignancies, but their efficacy in solid tumors has been limited due to the immunosuppressive tumor microenvironment. We found that cancer antigen-EpCAM expression increased in the metastatic stage compared with the primary stage in cancers. The activation of Wnt and TGFβ pathways was positively correlated with EpCAM expression in multiple cancers. We constructed CAR T cells targeting EpCAM that successfully showed selective cytotoxicity in highly EpCAM-expressing cancer cell lines. The combination of EpCAM CAR-T with the Wnt inhibitor-hsBCL9CT-24 displayed synergy in inhibiting tumor growth. A mechanistic study showed that hsBCL9CT-24 treatment could modulate the tumor environment and improve infiltration of T cells, while possibly promoting the effector T cells at the early stages and postponing the exhaustion of CAR T cells at advanced stages. Overall, these results demonstrated that the combination of the Wnt inhibitor with EpCAM CAR T-cell therapy can overcome the limitations of CAR T cells in treating solid tumors.